2019
DOI: 10.1038/s41467-019-09834-2
|View full text |Cite
|
Sign up to set email alerts
|

Molecular subtyping reveals immune alterations associated with progression of bronchial premalignant lesions

Abstract: Bronchial premalignant lesions (PMLs) are precursors of lung squamous cell carcinoma, but have variable outcome, and we lack tools to identify and treat PMLs at risk for progression to cancer. Here we report the identification of four molecular subtypes of PMLs with distinct differences in epithelial and immune processes based on RNA-Seq profiling of endobronchial biopsies from high-risk smokers. The Proliferative subtype is enriched with bronchial dysplasia and exhibits up-regulation of metabolic and cell cyc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
106
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(113 citation statements)
references
References 51 publications
7
106
0
Order By: Relevance
“…Estrogen targeting agents may therefore be especially effective in those patients with underlying inflammatory conditions such as chronic obstructive pulmonary disease or emphysema, who already show heightened immunosuppression. Since immune responses are also observed in very early lung premalignancies, hormonal modulation may play a role in the prevention setting as well (178,179). As an increased focus is being placed on the interaction between tumor cells and the cells within the TME, the role of estrogen within this context provides a unique perspective that can fit within this complex and constantly changing paradigm.…”
Section: Discussionmentioning
confidence: 99%
“…Estrogen targeting agents may therefore be especially effective in those patients with underlying inflammatory conditions such as chronic obstructive pulmonary disease or emphysema, who already show heightened immunosuppression. Since immune responses are also observed in very early lung premalignancies, hormonal modulation may play a role in the prevention setting as well (178,179). As an increased focus is being placed on the interaction between tumor cells and the cells within the TME, the role of estrogen within this context provides a unique perspective that can fit within this complex and constantly changing paradigm.…”
Section: Discussionmentioning
confidence: 99%
“…Heatmap analysis revealed that the 9 PKCi-SOX2 Eigengene genes are significantly and specifically overexpressed in Classical LSCC tumors (162/478 [34%] of LSCC tumors), whereas the 12 PKCi-ECT2 Eigengene genes are overexpressed in both Primitive and Classical LSCC subtypes ( Figure 4E). Analysis of a gene expression dataset of bronchial premalignant lesions (PMLs) (n = 431) that were classified into four molecular subtypes: Secretory, Normal-like, Inflammatory, and Proliferative (Beane et al, 2019), revealed significantly higher PKCi-SOX2 Eigengene scores in Proliferative PMLs compared to other subtypes ( Figure 4F), whereas PKCi-ECT2 Eigengene scores did not differ significantly across PML subtypes ( Figure 4G). Thus, PKCi-SOX2 signaling is preferentially activated in Proliferative PMLs, which exhibit a strong association with smoking behavior, increased histological progression to dysplasia, an elevated propensity to progress to LSSC, and genomic features consistent with the Classical subtype of LSCC tumors (Hammerman et al, 2012).…”
Section: Pkci-sox2 Regulated Genes Contribute To Transformed Growth Omentioning
confidence: 99%
“…After profiling the genomic, transcriptomic, and epigenomic landscape of those PMLs, the predictive value of specific geneexpression signatures, DNA methylation patterns and copy number alterations was confirmed for specific genes, which could be used to accurately determine the probability of CIS progression (267). Additionally, immune-specific subtypes of bronchial PMLs, LUSC precursors preceding CIS, were shown to correlate with their fate (268). Those that progressed into persistent lesions and henceforth LUSCs were characterized by downregulation of genes involved in interferon signaling and T cell-mediated immunity in comparison to regressive lesions, thus highlighting a dynamic interplay between epithelial and immune pathways early on in premalignant lesions (268).…”
Section: Immunogenomics For a Deeper Understanding Of Pmlsmentioning
confidence: 94%
“…Additionally, immune-specific subtypes of bronchial PMLs, LUSC precursors preceding CIS, were shown to correlate with their fate (268). Those that progressed into persistent lesions and henceforth LUSCs were characterized by downregulation of genes involved in interferon signaling and T cell-mediated immunity in comparison to regressive lesions, thus highlighting a dynamic interplay between epithelial and immune pathways early on in premalignant lesions (268). Taken together, these immunogenomics-based findings can provide strong evidence for the interplay between molecular aberrations and immune contexture early on in non-invasive lesions, providing a clinical window of opportunity to derive early detection, prognostic as well as prediction markers for better patient stratification and personalized immune prevention strategies in high risk individuals.…”
Section: Immunogenomics For a Deeper Understanding Of Pmlsmentioning
confidence: 99%